Faktor Penyebab Terjadinya Pembunuhan di Desa Upfaon Kabupaten Timor Tengah Utara - Petrus Giano Nepa; Rudepel Petrus Leo; Heryanto Amalo (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study is entitled Factors Causing Murder in Upfaon Village, North Central Timor Regency. This study aims to reveal the factors behind the occurrence of the crime of murder committed by a father against his son-in-law in Upfaon Village, South Biboki District, North Central Timor Regency. The method used is empirical juridical with a qualitative approach. The data used consists of primary, secondary, and tertiary data, which are obtained through literature studies and interviews with four respondents who have a direct connection to the case. Data analysis techniques are carried out through the stages of editing, coding, and tabulation, then analyzed descriptively qualitatively. The results of the study indicate that there are two main factors that cause the crime, namely internal and external factors. Internal factors include the emotional condition of the perpetrator such as heartache, anger, and revenge. While external factors are influenced by the consumption of alcohol and local culture that still maintains the values ​​of violence as a form of conflict resolution.